Advances in Protozoan Epigenetic Targets and Their Inhibitors for the Development of New Potential Drugs - Carlos Gaona-López; Lenci K. Vazquez-Jimenez; Alonzo Gonzalez-Gonzalez; Timoteo Delgado-Maldonado; Eyrá Ortiz-Pérez; Benjamín Nogueda-Torres; Adriana Moreno-Rodríguez; Karina Vázquez; Emma Saavedra; Gildardo Rivera (Pharmaceuticals, 2023)
Protozoan parasite diseases cause significant mortality and morbidity worldwide. Factors such as climate change, extreme poverty, migration, and a lack of life opportunities lead to the propagation of diseases classified as tropical or non-endemic. Although there are several drugs to combat parasitic diseases, strains resistant to routinely used drugs have been reported. In addition, many first-line drugs have adverse effects ranging from mild to severe, including potential carcinogenic effects. Therefore, new lead compounds are needed to combat these parasites. Although little has been studied regarding the epigenetic mechanisms in lower eukaryotes, it is believed that epigenetics plays an essential role in vital aspects of the organism, from controlling the life cycle to the expression of genes involved in pathogenicity. Therefore, using epigenetic targets to combat these parasites is foreseen as an area with great potential for development. This review summarizes the main known epigenetic mechanisms and their potential as therapeutics for a group of medically important protozoal parasites. Different epigenetic mechanisms are discussed, highlighting those that can be used for drug repositioning, such as histone post-translational modifications (HPTMs). Exclusive parasite targets are also emphasized, including the base J and DNA 6 mA. These two categories have the greatest potential for developing drugs to treat or eradicate these diseases.